Contributi per una flora vascolare di Toscana. III (143-180) - PERUZZI, LORENZO; BEDINI, GIANNI; VICIANI D (2011)
New localities and/or confirmations concerning 38 specific and subspecific plant taxa of Tuscan vascular flora, belonging to 29 genera and 23 families: Orlaya (Apiaceae), Ornithogalum (Asparagaceae), Tolpis (Asteraceae), Symphytum (Boraginaceae), Hornungia, Lepidium (Brassicaceae), Centranthus (Caprifoliaceae), Silene, Stellaria (Caryophyllaceae), Carex (Cyperaceae), Dryopteris (Dryopteridaceae), Monotropa (Ericaceae), Astragalus (Fabaceae), Hypericum (Hypericaceae), Crocus (Iridaceae), Isoëtes (Isoëtaceae), Clinopodium (Lamiaceae), Orobanche (Orobanchaceae), Osmunda (Osmundaceae), Linaria (Plantaginaceae), Arrhenatherum, Crypsis, Hyparrhenia, Rostraria, Vulpia (Poaceae), Groenlandia (Potamogetonaceae), Cheilanthes (Pteridaceae), Valantia (Rubiaceae), Viola (Violaceae). In the end, the conservation status of the units and eventual protection of the cited biotopes are discussed.